Faktor - Faktor Pendorong Peningkatan Pendapatan Asli Daerah ( Studi Pada Pemerintahan Kabupaten Banyumas ) - Sri Hartono; Bambang Agus Pramuka; Eliada Herwiyanti (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
This study aims to determine the factors driving the increase in local revenue (PAD) to the Government of Banyumas. This research was conducted at the Department of Revenue Financial Management and Asset Banyumas (DPPKAD). The study was conducted with a qualitative approach to the use of internal DPPKAD officials as informants to provide valid informations what drives revenue generating Banyumas. According to the results of research and analysis, several factors driving the increase in revenue Banyumas, among others: (1) The existence of local enterprises (BUMD) as a contributor to revenue, (2) existence of policies undertaken by the Government of Banyumas Regency relevant for collection of the PAD, (3) Reward System granted to the parties relating to the acceptance of PAD and (4) the innovation made as a driver of local revenue from PAD which includes (a) Conformation to the taxpayer, (b) The Integrated team, (c) Revaluated property and land value of Property tax, and (d) Perform Socialization of a Local Taxes.